2022
DOI: 10.1097/phm.0000000000001953
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of High-Frequency Repetitive Transcranial Magnetic Stimulation in Migraine

Abstract: The aim of the study was to evaluate the effectiveness of repetitive transcranial magnetic stimulation in migraine measured by decrease in pain severity or attack frequency. Methods: A search at the Cochrane Controlled Trials Register (CEN-TRAL), MEDLINE (via PubMed), Embase, CINAHL, Web of Science, and Scopus. The risk of systematic bias was rated by using the Cochrane domain-based quality assessment tool. A randomeffects model was used. Results: Of 434 identified records, 8 randomized control studies were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Finally, 7 studies were considered as meeting our inclusion criteria. [18][19][20][21][22][23][24] A flow chart of literature selection is shown in Figure 1.…”
Section: Results On Literature Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 7 studies were considered as meeting our inclusion criteria. [18][19][20][21][22][23][24] A flow chart of literature selection is shown in Figure 1.…”
Section: Results On Literature Selectionmentioning
confidence: 99%
“…Table 3 displays the results of evaluating methodological quality using the AMSTAR 2 tool. Among the 7 SRs, 4 were rated as moderate quality 19,[21][22][23] and 3 were rated as low quality 18,20,24 It was worth noting that items 2 and 7 received poor ratings. All the SRs included PICO components and 4 19,[21][22][23] reported study protocols in advance.…”
Section: Methodological Quality Of the Included Srsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, rTMS has been recommended by the International Federation of Clinical Neurophysiology for the management of neurological and psychiatric disorders [26], and evidence is now quickly increasing, highlighting that DLPFC-rTMS should relieve pain in patients with chronic pain conditions, including migraine [27], spinal cord injury [26], and fibromyalgia syndrome [28]. Actually, a recent meta-analysis found that high-frequency DLPFC stimulation is able to induce an analgesic effect in patients with chronic pain [29], but at present, the overwhelming majority of systematic reviews and meta-analyses on health-related consequences after TBI have focused on depression, memory, selective attention, and postconcussion syndrome [30][31][32], with far less attention given to neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%